KEMAH BUDAYA Di Desa Kertayasa - Firmansyah, Fachru Nur Fahmi; Mulyana, Deni Adi; Fadhlurrohman, M. Arif; I.P, A. Fadhilah; Reihansyah, Luthfi; Maolana, Rizki; Nurrohim, Fajar Dzikri; Kilten N, Karin (Jurnal Pengabdian Bisnis dan Akuntansi, 2023)
Pangandaran has a fairly high focus on development that supports tourism. This development includes physical development, human resources, and innovative tourism development based on local wisdom. With the slogan "Pangandaran is becoming a world-class tourist destination based on local wisdom," Pangandaran continues to improve in a better direction. In Kertayasa village, one of the villages in the Pangandara region, there is a business entity that operates in the world of tourism, especially in providing services and services. The agency is called BUMDes Guha Bau. BUMDes together with the village government are developing a new place called Palatar. BUMDes and Kertayasa village officials are currently trying to develop a platform with the Edvencamp concept to make Kertayasa village a tourist destination with selling power. For this reason, as a form of dedication, students from the Padjadjaran University Communication Science Study Program together with BUMDes Gua Bahu held a tourism camp to introduce the culture of Kertayasa Village, in the form of cultural arts performances.